2013
DOI: 10.1111/ddi.12145
|View full text |Cite
|
Sign up to set email alerts
|

The law of diminishing returns: woodland birds respond to native vegetation cover at multiple spatial scales and over time

Abstract: Aim To quantify at multiple spatial scales: (1) spatial dependence in several measures of aggregate bird biodiversity, (2) the role of native vegetation cover in explaining variation in aggregate bird biodiversity and (3) relationships between change over 8 years in bird diversity and changes in native vegetation.Location South-eastern Australia.Methods We gathered data on birds between 2002 and 2010 on 184 (2 ha) sites nested within 46 (1000 ha) farms nested within 23 (10,000 ha) landscapes. We statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…Previous research within the study region has shown that bird species richness is related to vegetation cover at each of these scales [23]. To measure vegetation cover in each year, we used grids of Forest Extent (FE) derived from Landsat TM and MSS satellite imagery from 2002 and 2008 (see [42] for a detailed description of the satellite imagery specifications).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research within the study region has shown that bird species richness is related to vegetation cover at each of these scales [23]. To measure vegetation cover in each year, we used grids of Forest Extent (FE) derived from Landsat TM and MSS satellite imagery from 2002 and 2008 (see [42] for a detailed description of the satellite imagery specifications).…”
Section: Methodsmentioning
confidence: 99%
“…That is, is inference spatially limited or extensive? The large array of sites, farms and landscapes in our quasi-experiment on the South West Slopes of New South Wales represent the range of environments across the entire bioregion [42,43], and the study therefore has extensive inference over several million hectares. Conversely, the scope of inference of our landscape studies in the unique range of habitats at Booderee National Park is relevant only to that 6600 ha in that reserve [44,45].…”
Section: Structural Featuresmentioning
confidence: 99%
“…The hierarchical design encompasses 23 landscapes (with and without restoration plantings, with 12 landscapes in one region and 11 in another), two farms within those 23 landscapes (farms with and without restoration plantings) and four sites located on the 46 farms within the 23 landscapes (comprising plantings and remnant woodland patches) [38]. This design provided a powerful basis from which to make inferences about the impacts of planting on biodiversity at the landscape, farm and site levels [42,43]. A final key question is: Is there inefficient use of limited resources?…”
Section: Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Although there is presumably not a single 'best' spatial scale at which to associate species and their habitats for all species or ecological conditions, it is possible to reveal relevant ecological associations when the scale of analysis approaches the operational scale of the process of interest. Studies often use expert knowledge to set the scale of analysis, or in some cases use expert-informed designs to collect data at 'fine-' versus 'large-' spatial scales to compare their relative explanatory power (e.g., Saab 1999;Coppeto et al 2006;Cunningham et al 2014). Unfortunately, information regarding the ecological processes shaping the distribution or abundance of a species is often lacking, let alone the spatial scale at which these processes may act.…”
Section: Introductionmentioning
confidence: 99%